2020
DOI: 10.1021/acschemneuro.0c00360
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of the Binding Dynamics of Oligo p-Phenylene Ethynylene Fluorescence Sensors and Aβ Oligomers

Abstract: Amyloid protein aggregates are pathological hallmarks of neurodegenerative disorders such as Alzheimer's (AD) and Parkinson's (PD) diseases and are believed to be formed well before the onset of neurodegeneration and cognitive impairment. Monitoring the course of protein aggregation is thus vital to understanding and combating these diseases. We have recently demonstrated that a novel class of fluorescence sensors, oligomeric pphenylene ethynylene (PE)-based electrolytes (OPEs) selectively bind to and detect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…After 100 ns of simulation, 11 out of 12 OPE became bound to the protofibril at six different binding sites either as single OPE molecules (sites 1, 4, and 5) or as OPE complexes (sites 2, 3, and 6) (Figure A). This binding pattern is consistent with what we have previously reported in a MD simulation study, where hydrophobic and electrostatic interactions were the main driving forces for binding. Three of the binding sites were located on the β-sheet rich protofibril surface (sites 2, 3, and 6; Figure B,C); one was located on the β-turn (site 5; Figure D), and the last two were at the ends of the protofibril (sites 1 and 4; Figure B,E).…”
Section: Resultssupporting
confidence: 92%
“…After 100 ns of simulation, 11 out of 12 OPE became bound to the protofibril at six different binding sites either as single OPE molecules (sites 1, 4, and 5) or as OPE complexes (sites 2, 3, and 6) (Figure A). This binding pattern is consistent with what we have previously reported in a MD simulation study, where hydrophobic and electrostatic interactions were the main driving forces for binding. Three of the binding sites were located on the β-sheet rich protofibril surface (sites 2, 3, and 6; Figure B,C); one was located on the β-turn (site 5; Figure D), and the last two were at the ends of the protofibril (sites 1 and 4; Figure B,E).…”
Section: Resultssupporting
confidence: 92%
“…Very recently, Evans et al [ 41 ] carried out a computational investigation about the binding dynamics of compounds 19c and 18e ( Table 1 ) toward some Aβ oligomer models using classical all-atom molecular dynamics, in order to understand their interaction with amyloids. The studies were conducted with two β-sheet rich Aβ oligopeptides of 5- and 24-mer.…”
Section: Optical Properties Of Opesmentioning
confidence: 99%
“…All these features have been found to be important in OPE's water solubility, photophysical properties, and affinity and selectivity for aggregated protein conformations [14][15][16]21]. Results from simulation studies showed that OPEs bind to protein assemblies such as viral capsids [43] and Aβ40 protofibrils [44] at multiple sites. Binding free energy is dominated by strong van der Waals interactions between the hydrophobic OPE backbone and hydrophobic grooves and patches on the protein surface and favorable electrostatic interactions between the charged moieties on the OPEs and oppositely charged residues around the binding sites on the protein assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Binding free energy is dominated by strong van der Waals interactions between the hydrophobic OPE backbone and hydrophobic grooves and patches on the protein surface and favorable electrostatic interactions between the charged moieties on the OPEs and oppositely charged residues around the binding sites on the protein assemblies. Both anionic and cationic OPEs exhibit favorable interactions with Aβ oligomers [44]. Therefore, OPEs are viable as broad protein aggregate sensors and have diagnostic potential against AD and related proteinopathies.…”
Section: Introductionmentioning
confidence: 99%